The Effect of Organic Fertilizer Plus Micro Fertilizer on Soybean Plant Growth and Yield - Agus Priyanto; Aliya Aitenova; Zavalishina Anna (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the effect of organic fertilizer combined with micro fertilizers on the growth and yield of several soybean varieties cultivated in an agroforestry system under mango trees, as well as to evaluate the potential for developing soybean varieties in these land conditions. Methodology: The study used a field experiment with a two-factorial Randomized Complete Block Design. Materials included soybean seeds of the Grobogan, Anjasmara, Argomulyo, and Mutiara varieties, manure, and microfertilizers. Tools used included a hand sprayer, light meter, thermohygrometer, oven, analytical balance, and camera. Data were analyzed using ANOVA and further Duncan Multiple Range Test (DMRT) at the 5% level. Main Findings: All soybean varieties demonstrated adaptability to agroforestry systems under mango stands, although productivity remained low. The Anjasmara variety produced the highest seed weight, while the Mutiara variety had the highest 100-seed weight. Neither organic fertilizer treatment of 5 tons/ha nor a combination of organic fertilizer and microfertilizers significantly affected soybean growth and yield. Varietal factors significantly affected only 100-seed weight. Novelty/Originality of this study: The novelty of this research lies in the evaluation of the combination of organic fertilizer and microfertilizer on several soybean varieties in an agroforestry system under mango trees. This study provides new information on the response of soybean varieties to shade conditions and the effectiveness of integrated fertilization, thus expanding knowledge on sustainable soybean cultivation strategies in agroforestry areas.